FISIKA DALAM PERMAINAN BOLA VOLI: PENGARUH BESAR SUDUT TERHADAP SERVIS BAWAH DITINJAU DARI GERAK PARABOLA - Camelia Azzahra; Entin Halimah Subekti; Bayu Setiaji (Universitas Jember, 2023)
Parabolic motion is the curved motion of an object whose trajectory is a parabola. In objects that experience parabolic motion, objects will experience the farthest distance and the highest point. The farthest distance traveled by an object in motion with a parabolic trajectory is influenced by the elevation angle formed, this is because the velocity in the direction of the x-axis and the velocity in the direction of the y-axis are affected by the magnitude of the angle of elevation formed. The purpose of this study is to analyze the motion of the parabola on the volleyball serve with a variety of different angles so that volleyball players can find out the ideal angle for the under serve so that the ball can fall on target and over the net. This research is using experimental method. The results of a good and ideal angle when serving under a volleyball so that the ball falls on target and crosses the net using an initial angle of 600, a falling angle of 250, and with a speed of 11.2 m/s which is analyzed using a tracker.